Social Theory and Everyday Marxists: Russian Perspectives on Epistemology and Ethics. (29th September 2017) - Kruglova, Anna
Abstract: Scholars have long tracked how the USSR, a laboratory of social engineering, was deeply informed by local readings of Marxist social theory. Why, then, in recent years, have so many historical and anthropological studies of Russia excluded "Marxist" from the list of main descriptors, or optics, through which they view their material? In this essay, I argue that in much contemporary scholarship Marxism and its many afterlives have evidenced a kind of blind spot, reducing Marxism to "just" an ideology. I assert that rediscovering the presence of Marxism in Russia as a Gramscian hegemonic process and a vernacular that emerged among "laymen" can help us understand how a wide range of Russians continue to make sense of their worlds today. Drawing on several years of research in the city of Perm, I interpret everyday conversations among middle-age urbanites about morality, and demonstrate how this rediscovery of Marxism can elucidate what things matter for Russians today, and how. If social scientists proceed by acknowledging that "professional" and "lay" social knowledge increasingly share sources of "theoretical" inspiration, then we face a range of narrative challenges.